2015
DOI: 10.1186/s40623-015-0183-5
|View full text |Cite|
|
Sign up to set email alerts
|

A case study on occurrence of an unusual structure in the sodium layer over Gadanki, India

Abstract: The height-time-concentration map of neutral sodium (Na) atoms measured by a Na lidar during the night of 18 to 19 March 2007 over Gadanki, India (13.5°N, 79.2°E) reveals an unusual structure in the Na layer for around 30 min in the altitude range of 92 to 98 km which is similar to the usual 'C' type structures observed at other locations. In order to understand the physical mechanism behind the generation of this unusual event, an investigation is carried out combining the data from multiple instruments that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 53 publications
(70 reference statements)
0
4
0
Order By: Relevance
“…The C‐type structures observed in the lidargram on several occasions could be caused by wave breaking or KH billows and may be generated in the Na layer due to strong wind shear (Kane et al, ). As described in Sarkhel et al (), a KH billow structure can imprint a C‐type structure in the lidargram. Therefore, in order to judge the persistence of the C‐type in the lidargram, the evolution of KH billows needs to be investigated.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The C‐type structures observed in the lidargram on several occasions could be caused by wave breaking or KH billows and may be generated in the Na layer due to strong wind shear (Kane et al, ). As described in Sarkhel et al (), a KH billow structure can imprint a C‐type structure in the lidargram. Therefore, in order to judge the persistence of the C‐type in the lidargram, the evolution of KH billows needs to be investigated.…”
Section: Discussionmentioning
confidence: 92%
“…Therefore, Sridharan et al () supported the hypothesis, proposed by Kane et al (), of KH instability for the formation of complex sporadic structures. Sarkhel et al (, ) have examined the Na lidargram from Gadanki, India, on a night using a meteor radar from Thiruvananthapuram, India, and satellite borne measurements. They suggested that the KH billow formation took place over Thiruvananthapuram, southern part of India.…”
Section: Introductionmentioning
confidence: 99%
“…However, the ducting inhibits the vertical propagation of GWs and confines the major flow of wave energy and momentum to a rather limited altitude region (Chimonas and Hines, 1986). The earlier imaging studies using airglow emissions originating in the MLT region revealed different types of dynamical events like quasi-monochromatic GWs, ripples, and mesospheric fronts (Taylor et al, 1995;Walterscheid et al, 1999;Hecht et al, 2001;Smith et al, 2003;Makhlouf et al, 1995;Bageston et al, 2011;Lakshmi Narayanan et al, 2012;Sarkhel et al, 2012Sarkhel et al, , 2015aSarkhel et al, , b, 2019Hozumi et al, 2019;Mondal et al, 2021;Guharay et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have suggested dynamical instability to be related to these complex structures e.g., [5][6][7]. Dynamical instability refers to a process in which the atmosphere becomes unstable and its movement cannot be considered a laminar fluid.…”
Section: Introductionmentioning
confidence: 99%